2012
DOI: 10.1108/02656711211270342
|View full text |Cite
|
Sign up to set email alerts
|

The impact of upstream supply and downstream demand integration on quality management and quality performance

Abstract: PurposeThere are many studies on the impact of supply chain integration (SCI) on performance. However, the definitions, the measurements, the sample sizes, and scope of both SCI and the performance vary significantly from research to research. Conclusions are not consistent either. Researchers still believe that little is known about the impact of SCI on performance and call for more empirical research. The purpose of this paper is to investigate the impact on quality practices and quality performance of upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…However, the definitions, the measurements, the sample sizes, and scope of both SCI and the performance vary significantly from research to research. Conclusions are not consistent either (Sun and Ni 2012). Researchers still believe that little is known about the impact of SCI on performance and call for more empirical research.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the definitions, the measurements, the sample sizes, and scope of both SCI and the performance vary significantly from research to research. Conclusions are not consistent either (Sun and Ni 2012). Researchers still believe that little is known about the impact of SCI on performance and call for more empirical research.…”
Section: Introductionmentioning
confidence: 88%
“…Some of them define integration as upstream (with suppliers) and downstream (with customers) (Frohlich and Westbrook 2001;Sun andNi 2012, internal or external Richey et al 2009), integration with supplier and customer and internal (Lee et al 2007;Boon-itt and Wong 2011;Huo 2012) so on. Kannan and Tan (2010) extended the discussion of integration to explicitly incorporated firms beyond first tier suppliers and customers.…”
Section: The Scope Of Supply Chain Integrationmentioning
confidence: 98%
See 1 more Smart Citation
“…Some authors claimed that internal integration is prerequisite to external integration (Horn, Scheffler, & Schiele, 2014) and the dimensions of SCI in the past literature were not consistent. For instance, Narasimhan and Kim (2002) operationalized supply chain integration from the aspect of internal and external integration, and meanwhile some authors have only considered internal integration (Foerstl, Hartmann, Wynstra, & Moser, 2013;Pagell, 2004) or external integration (Koufteros, Edwin Cheng, & Lai, 2007;Sun, 2012) in their studies. Importantly, most of supply chain integration studies revealed that there is association between supply chain integration and firm performance (Flynn et al, 2010;Rajagopal, Zailani, & Sulaiman, 2009).…”
Section: Literature Review and Proposed Research Frameworkmentioning
confidence: 99%
“…Internal integration is regarded as supply chain activities that are carried out by several functions within the firms (Flynn, Huo, & Zhao, 2010). Meanwhile, external integration is generally referred to the integration among supply chain partners across firm's boundaries that encompasses of upstream and downstream supply chain (Sun, 2012) with the aim is to create value to the entire supply chain. Some authors claimed that internal integration is prerequisite to external integration (Horn, Scheffler, & Schiele, 2014) and the dimensions of SCI in the past literature were not consistent.…”
Section: Literature Review and Proposed Research Frameworkmentioning
confidence: 99%